Evaluation of corn cob-derived microfibrillated cellulose for use as oil/water emulsion stabilizer - Tang, Teck Kim (2020)
Environmental pollution has become a main concern in recent years. In developing countries, the main agricultural waste consisting of low value fiber/lignocellulose material are underutilized. Instead, burning of these materials for replanting purposes has become a norm in some countries, creating a huge air pollution almost every year. Hence, creating new usage and value-added compound from this lignocellulose material by employing a simple method yet environmental-friendly approach may indirectly increase the value of the fiber/lignocellulose material and reduce environmental problems. Corn cob, an agricultural waste has the potential to produce a type of nanocellulose called microfibrillated cellulose (MFC) which can be used as an emulsion stabilizer. Previously, such microfibrillated cellulose were prepared using wood pulp as main raw material and chemical pretreatment is the easiest way to pretreat the fiber. However, extensive usage of the chemicals for pretreatment creates environmental problems. Therefore, in the present study, a simple, milder and environmentally-friendly pretreatment process of corn cob was developed to convert corn cob into MFC prior to assessing and characterizing their ability to stabilize oil-in-water emulsion. In the approach, a lower dosage of sodium hydroxide pretreatment was successfully developed by response surface methodology before the treated corncob fibers were biobleached with xylanase. The color of the pretreated corn cob fiber/pulp was found to be enhanced and the use of enzyme-assisted biobleaching reduced the amount of chlorine-based bleach used. The treated pulp were then subjected to mild hydrolysis process using endoglucanase to facilitate the extraction of MFC through high pressure homogenization. It was found that the lowest concentration of endoglucanase was able to prevent blockage of the high pressure homogenizer unit and at the same time still preserved the intact structure of cellulose fiber. Subsequently, different cycles of high pressure homogenization were employed for the production of MFC. The water holding capacity, and resistance toward evaporation of MFC suspension were improved with the increased of high pressure homogenization cycle. MFC produced had increased shear viscosity and gelation properties due to its ability to form a network-like structure in suspension. These MFC were then used to test its emulsion stabilizing efficiency. All MFC-stabilized emulsion produced showed shear thinning effect and its shear viscosity increased with ii homogenization cycle. The results also showed that MFC-stabilized emulsions were extremely stable under normal storage conditions at different temperatures from 5°C to 45°C. All the characteristics mentioned above indicated that MFC has high potential to be used as thickening agent or stabilizer in many food, cosmeceutical and pharmaceutical products.